Diagnostic Value of Coproantigen for Detection of Giardia Infection in Stunted Children - Octoviani, Fanny Anggraeni; Kurniawan, Agnes; Sari, Ika Puspa; Fauziah, Nisa; Faridah, Lia; Adrizain, Riyadi (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Giardiasis is a protozoa infection caused by Giardia intestinalis, which commonly infects children, impairing children’s growth, development, and cognitive function. Standard diagnosis is carried out by microscopic examination of stool. This study aimed to evaluate coproantigen examination in stunted children compared to microscopic examination.Methods: A cross-sectional study was performed on stools collected from a survey among stunted children in Bandung in 2019. Stools were preserved in 10% formaldehyde and kept at -20oC until used. Direct microscopy examination with 2% lugol solution and coproantigen ELISA test using Giardia Cryptosporidium (combo test) coproantigen test kit were performed in Parasitology Laboratory Faculty of Medicine, Universitas Indonesia.Result: A total of 99 stools originated from stunted children aged 2-6 years. with boys predominant (52.5%). Microscopic examination showed that 12.1% (12/99) of the children were harboring intestinal parasites, such as the protozoa Giardia intestinalis, Blastocystis spp, and Entamoeba coli (E. coli). Giardia was the primary infection (9.1%), of which single Giardia infection (n = 8) and mixed infection of Giardia and Blastocystis spp (n = 1). Interestingly, coproantigen examination resulted in 6 positive samples, and 4 samples agreed with the microscopy result. With a sensitivity of 44.4% and a specificity of 97.7%. The positive and negative predictive values were 66.7% and 94.7%, respectively.Conclusion: A moderate prevalence of Giardia in stunted children in Bandung regency has been observed. The combo coproantigen test method has high specificity and is suitable for use as a confirmation test to exclude Giardia infection.